Răspuns:
Gasesti mai jos rezolvarea completa.
Explicație pas cu pas:
a) a / 19 + 11a / 19 + 7a / 19 = (a + 11a + 7a) / 19 = 19a / 19 = a
b) 3a / 23 + 17a / 23 + 26a / 23 = (3a + 17a + 26a) / 23 = 46a / 23 = 2a
c) 11x / 49 + 13x / 49 + 25x / 49 = (11x + 13x + 25x) / 49 = 49x / 49 = x
d) 15b / 7 - 3b / 7 - 5b / 7 = (15b - 3b - 5b) / 7 = 7b / 7 = b
e) 21y / 11 - 7y / 11 - 3y / 11 = (21y - 7y - 3y) / 11 = 11y / 11 = y
f) 29c / 47 - 21c / 47 - 8c / 47 = (29c - 21c - 8c) / 47 = 0 / 47 = 0
Sper ca te-am ajutat.